Agricultural and Fishery Activities on Mangrove Ecosystem Area, Bekasi Regency: Exploration Studies of Land Use Conditions in The Coastline Buffer Area - Rahmawati, Azelia Dwi; Asy’Ari, Rahmat; Dzulfigar, Ali; Destia, RA. Aulia Fitri; Ananda, Rizkhy; Faridah, Dedeh; Adila, Julita Catri; Firmansyah, Lalita Mahardika Putri; Marfi, Khairani Putri; Puspitasari, Raditya Febri; Ulfa, Aulia; Puspita, Sylva; et al. (SSRS Journal A: Agro-Environmental Research, 2024)
As a country with the widest mangrove forest area in the world, Indonesia has potential and challenges in preserving the mangrove ecosystem. Bekasi Regency is an area with a mangrove ecosystem that has experienced degradation, so research needs to be conducted to monitor the mangrove area and uncover land use by coastal communities. This research uses field data (including agricultural and fishing activities) in mangrove forest area in Bekasi Coastline Buffer Area, and remote sensing data from Sentinel-2 MultiSpectral Instrument (MSI) satellite data. In process analysis, using machine learning (ML) algorithm is the Support Vector Machine (SVM) and through in the advanced GEE computing platform. The analysis involves 11 indices consisting of vegetation indices, namely NDI, MNDVI, SAVI, SLAVI, and ARVI; water indices, namely NDWI, LSWI, and ANDWI; and building indices, namely IBI. The results of mangrove mapping obtained an area of ​​836.91 ha or equivalent to 6.57% of the area of ​​Bekasi Regency and the Overall Accuracy (OA) results reached 90%, and Kappa Statistics (KS) were 0.8. The mapped mangrove areas have great potential in various aspects, especially playing a role in controlling land erosion, protecting against atmospheric disasters, and also contributing to controlling climate change. The silvofishery area which is a balance between mangroves and ponds, has great potential in sustainable land use and coastal ecosystem restoration.This research is expected to encourage policymakers to become one of the strategic policy supports that can quickly restore the mangrove ecosystem, thus controlling the threat of sea-level inundation that adds to the vulnerability area every year.